Preparation method of enhanced biaxially oriented polyester film

By PMMA grafting and PDMS coating of nano titanium dioxide particles, and graded shear blending in PET resin, the problem of uneven dispersion of nano particles was solved and the puncture resistance of the polyester film was significantly improved.

CN119331289AInactive Publication Date: 2025-01-21ZHEJIANG HUAQING NEW MATERIALS CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411850753.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the dispersion of nanoparticles in the polyester film matrix is ​​uneven, resulting in insufficient puncture resistance.

Method used

By pre-treatment, PMMA grafting and layer-by-layer PDMS coating of nano-titanium dioxide particles, dual-modified nano-titanium dioxide particles are formed, and they are graded shear blended in PET resin to improve their dispersion in the film. Uniformity and puncture resistance.

Benefits of technology

The uniform dispersing of nano -titanium sorbexan particles in PET resin significantly improves the anti -puncture performance of a two -way stretch polyester film, and avoids the cracking and peeling of the branches and overwriting layers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of an enhanced biaxially oriented polyester film, belongs to the field of polyester film preparation, and solves the problems that in the prior art, nanoparticles are easy to agglomerate in the mixing process of the nanoparticles and polyester, so that the dispersion is not uniform, and the puncture resistance of the film is finally influenced. The preparation method comprises the following steps: 1, pretreating nano titanium dioxide particles, and uniformly dispersing the nano titanium dioxide particles; step 2, carrying out PMMA (Polymethyl Methacrylate) grafting treatment on the pretreated nano titanium dioxide particles; 3, the nano titanium dioxide particles subjected to PMMA grafting treatment are sequentially subjected to dip-coating layer by layer in a PDMS solution with the concentration being 10 wt%, a PDMS solution with the concentration being 15 wt% and a PDMS solution with the concentration being 20 wt%, and dual-modified nano titanium dioxide particles are obtained; step 4, adding the double modified nano titanium dioxide particles into pet resin, and carrying out graded shearing and blending; the technical effect of improving the dispersion uniformity of the nanoparticles in the matrix and the puncture resistance of the biaxially oriented polyester film is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester film preparation, and in particular relates to a method for preparing an enhanced biaxially oriented polyester film. Background Art

[0002] Biaxially oriented polyester film is a film made of polyethylene terephthalate (PET), which is processed by stretching in the longitudinal and transverse directions simultaneously or successively. Biaxial stretching makes the film have high strength and excellent mechanical properties in both directions, so BOPET film has excellent tensile strength, tear resistance, stability, transparency and heat resistance.

[0003] In the prior art, in order to improve the puncture resistance of polyester film, the patent "A Nanoparticle-Biodegradable Polyester Film and Its Preparation Method" (CN116218165A) provides a method for improving the PBART film by adding nanoparticles. Specifically, inorganic non-metallic nanoparticles are selected to form a 3D network structure of polyester and nanoparticles, thereby improving the mechanical properties of the film, especially the puncture resistance.

[0004] The patent "A Biaxially Stretch Polyethylene Anti-fog Film" (CN113927982A) discloses a method of reducing the crystal growth rate of polyethylene by forming a styrene-lauryl methacrylate copolymer on the surface of titanium dioxide, thereby reducing the haze of the film and improving the uniformity and film-forming properties of the film. This technology of first grafting and then modifying is relatively common. The main purpose of the grafted layer is to increase the bonding strength between titanium dioxide and the coating layer, and at the same time modify the surface of titanium dioxide from hydrophilic to lipophilic, thereby increasing the solubility of titanium dioxide in the matrix. However, the improvement of the dispersibility of titanium dioxide in the organic matrix is ​​relatively limited. For external puncture, its coating layer is more like a rigid coating layer and cannot achieve stress dispersion for titanium dioxide.

[0005] The patent "Method for preparing grafted nano-titanium dioxide particles" (CN101353180B) discloses a technology for grafting methyl acrylate (MMA) on the surface of titanium dioxide. This technology can achieve graft modification of titanium dioxide. However, compared with directly putting the modified titanium dioxide into the biaxially oriented polyester film, although it can improve the dispersibility of titanium dioxide particles in PET, under the action of stress, the rigid and brittle graft layer is prone to cracking, resulting in the peeling of the graft layer and the nano-titanium dioxide particles. At the same time, under the high temperature processing of the biaxially oriented polyester film, agglomeration still occurs. The patent "A method for preparing nano titanium dioxide, nano titanium dioxide and its application" (CN112645382B) discloses a technology for coating the surface of titanium dioxide with polydimethylsiloxane. This technology can form a flexible coating layer on the surface of titanium dioxide. The technical effect achieved is to improve the light transmittance and modify the surface properties of nano titanium dioxide. The above two technical effects are mainly to coat the surface of the nanoparticle precursor with a layer of organic matter by emulsification treatment first, and then form nano titanium dioxide by calcination, and at the same time carbonize the organic matter on the surface of titanium dioxide, thereby preventing the alignment and agglomeration. The PDMS coating layer in this technology only plays the role of further improving the dispersibility, and does not play a decisive role (as can be seen from its comparative example 2), and there is no research on the mechanical properties of the particles.

[0006] In summary, there are few studies in the prior art on the application of PMMMA and PDMS in polyester films, and the application of nano-titanium dioxide in the combination mechanism of the above two substances. Summary of the invention

[0007] In view of the problem of uneven dispersion of nanoparticles in a matrix in the prior art, the present invention provides an enhanced biaxially oriented polyester film and a preparation method thereof, the purpose of which is to improve the dispersion uniformity of nanoparticles in the matrix and the puncture resistance of the biaxially oriented polyester film.

[0008] The technical solution adopted by the present invention is as follows: 1. A method for preparing a reinforced biaxially oriented polyester film comprises the following steps: Step 1: pretreating the nano titanium dioxide particles and uniformly dispersing the nano titanium dioxide particles; Step 2: performing PMMA grafting treatment on the pretreated nano-titanium dioxide particles; Step 3: dip-coating the PMMA-grafted nano-titanium dioxide particles layer by layer in 10wt%, 15wt%, and 20wt% PDMS solutions in turn to obtain double-modified nano-titanium dioxide particles; Step 4: adding the double modified nano titanium dioxide particles into the pet resin and performing graded shear blending; Step 5: Optimize the biaxial stretching of the blended PET resin; The enhanced biaxially oriented polyester film comprises: PET resin; double-modified nano titanium dioxide particles are uniformly dispersed in the PET resin; The surface of the double-modified nano titanium dioxide particles is grafted with a PMMA layer, and the PMMA layer is coated with a PDMS layer outside; a first transition layer and a second transition layer are sandwiched between the PMMA layer and the PDMS layer, and the PDMS content in the second transition layer is higher than that in the first transition layer; Among them, PET resin 94-98wt%; nano titanium dioxide particles 0.1-5wt%; PMMA polymer 1-2wt%; PDMS polymer 0.5-2wt%; platinum-based catalyst 0.005-0.05wt%.

[0009] By adopting the above scheme, a PMMA layer and a PDMS layer are formed on the surface of the nano-titanium dioxide, wherein the PMMA layer has rigidity and polarity properties, and can form a rigid protective layer on the surface of the nano-titanium dioxide to improve the mechanical properties of the nano-titanium dioxide, and make the particles more easily dispersed in the PET through its polarity; the PDMS layer coated on the surface of the PMMA layer can prevent the van der Waals force aggregation phenomenon between the particles; the PDMS layer coated on the surface of the PMMA layer can also disperse the stress for the rigid PMMA layer with its flexible property, thereby avoiding the PDMS layer from cracking and peeling off the nano-titanium dioxide particles due to the action of external force. In the combination of PMMA and PDMS, since the expansion coefficients of PMMA and PDMS are relatively large, they are easily separated during the high-temperature processing of the biaxially stretched polyester film. The expansion of PDMS causes stress to be generated at the interface between PMMA and PMDS, thereby fracturing PMMA and generating cracks, reducing the mechanical properties of the particles and causing reagglomeration due to the van der Waals force between the particles. When forming the PDMS coating layer, a layer-by-layer coating method with gradually increasing concentration is adopted. This method forms several layers of coating layers with different PDMS contents on the outside of the PMMA layer, wherein the coating layer in contact with the PMMA layer has the lowest PDMS content, and the PDMS content in the coating layer gradually increases in the direction away from PMMA. This structure can form several buffer layers between the PDMS layer with the highest concentration and the PMMA layer, avoiding the high-concentration PDMS layer from fracturing the PMMA layer due to excessive expansion, while also retaining a good bond between the PMMA layer and the PDMS layer.

[0010] Furthermore, the specific steps of step 1 are: Nano-titanium dioxide particles were added into anhydrous ethanol and dispersed by ultrasonic for 20 minutes to ensure that the nano-particles were evenly dispersed.

[0011] Furthermore, the specific steps of step 2 are: Step 21: Add MMA to the pretreated nano-titanium dioxide solution and continue to stir evenly; Step 22: Add AIBN as an initiator, maintain the solution temperature at 60°C-75°C, and stir under the protection of protective gas. The reaction lasts for 3-5 hours. This step will generate PMMA chains and graft them onto the surface of nano-titanium dioxide particles; Step 23: After the reaction in step 22 is completed, the solvent is removed by rotary evaporation to obtain grafted modified nano titanium dioxide particles, and the particles are dried at 55°C-65°C for 12 hours to ensure that the ethanol is completely evaporated.

[0012] The specific steps of step 3 are: Step 31: immersing the grafted modified nano-titanium dioxide particles into a 10wt% PDMS solution for dip coating, and adding 0.01-0.05wt% of a platinum-based catalyst into the solution to promote cross-linking, wherein the dip coating speed is 1-5mm / s and the pulling speed is 1-2mm / s; Step 32: Curing the dip-coated nano-titanium dioxide particles at 70-80° C. for 10 minutes; Step 33: Replace the concentration of the PDMS solution with 15wt% and 20wt% respectively, and repeat steps 31 and 32 to obtain double-modified nano-titanium dioxide particles.

[0013] Step 34: After the reaction in step 33 is completed, the coated nano-titanium dioxide particles are collected by centrifugation, washed with ethanol three times to remove excess PDMS, and finally vacuum dried at 70° C. for 6 hours.

[0014] The specific steps of step 4 are: Step 41: Add the double modified nano titanium dioxide particles and pet resin into the blender, set the screw speed to 255-265 rpm, control the temperature to 270-280°C, and maintain for 5-10 minutes; Step 42: After completing step 41, set the screw speed to 270-285 rpm and the temperature to 280-290°C for 5-20 minutes; Step 43: After completing step 42, control the blender to slowly reach room temperature to complete the mixing of the double-modified nano titanium dioxide particles and the PET resin.

[0015] The above scheme is adopted, in which the graded shearing is first pre-mixed by low-speed shearing to evenly disperse the nano titanium dioxide particles in the PET resin to initially achieve the wetting and distribution of the particles; then the particles are further broken up by high shear rate to avoid aggregation between particles; through the graded shearing process, the thickness of the grafted layer and the coating layer can be easier to control, and the speed control at different shearing stages can ensure that the coating thickness is uniform and moderate, avoiding mechanical property problems caused by excessive or uneven coating.

[0016] A reinforced biaxially oriented polyester film, comprising PET resin: The PET resin is uniformly dispersed with double-modified nano titanium dioxide particles; The surface of the double-modified nano titanium dioxide particles is grafted with a PMMA layer, and the PMMA layer is coated with a PDMS layer on the outside; Among them, PET resin 94-98wt%; nano titanium dioxide particles 0.1-5wt%; PMMA polymer 1-2wt%; PDMS polymer 0.5-2%; platinum-based catalyst 0.005-0.05%.

[0017] By adopting the above scheme, the double-modified nano-titanium dioxide in the pet polyester film can play the role of hard particles in the biaxially stretched polyester film. When punctured, these nano-particles can become the supporting points of the film and effectively resist the puncture pressure; the nano-titanium dioxide particles with a PMMA layer and a PDMS layer on the surface can share part of the external force during the puncture process, and transmit the force to the substrate through a flexible coating layer and a highly compatible grafting layer, thereby forming a stronger puncture-resistant structure; the PMMA layer grafted on the surface of the nano-titanium dioxide particles can improve the compatibility of the nano-titanium dioxide particles with the pet resin and improve the dispersion uniformity of the nano-titanium dioxide particles in the pet resin, the PDMS coating layer can prevent direct contact between particles and reduce agglomeration, and the platinum-based catalyst can improve the mechanical strength and durability of the PDMS coating layer and improve the interface bonding force between the PMMA layer and the PDMS layer.

[0018] Furthermore, the average particle size of the double-modified nano titanium dioxide particles is 20-50 nm.

[0019] Furthermore, the specific surface area of ​​the double-modified nano titanium dioxide particles is 110-120 / g. .

[0020] Furthermore, the polyester film is subjected to biaxial stretching treatment, with the stretching ratio being 3.5 times in the longitudinal direction and 3 times in the transverse direction.

[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. Form a PMMA layer and a PDMS layer on the surface of nano-titanium dioxide, wherein the PMMA layer has rigid and polar properties, and can form a rigid protective layer on the surface of nano-titanium dioxide to improve the mechanical properties of nano-titanium dioxide, and make the particles more easily dispersed in PET through its polar properties; the PDMS layer coated on the surface of the PMMA layer can prevent the van der Waals force aggregation phenomenon between the particles; the PDMS layer coated on the surface of the PMMA layer can also disperse the stress for the rigid PMMA layer with its flexible properties, thereby avoiding the PDMS layer from cracking and peeling off due to external forces. Nano-titanium dioxide particles, in the combination of PMMA and PDMS, due to the large expansion coefficients of PMMA and PDMS, are easily damaged during the high-temperature processing of biaxially stretched polyester film due to PDMS. The expansion of MS causes stress to be generated at the interface between PMMA and PMDS, which causes PMMA to be crushed and cracked, reducing the mechanical properties of the particles and causing the Van der Waals force between the particles to re-agglomerate; when forming the PDMS coating layer, a coating method with gradually increasing concentration is adopted, which forms several coating layers with different PDMS contents on the outside of the PMMA layer, wherein the coating layer in contact with the PMMA layer has the lowest PDMS content, and the PDMS content in the coating layer gradually increases along the direction away from PMMA. This structure can form several buffer layers between the PDMS layer with the highest concentration and the PMMA layer, avoiding the PMMA layer from being crushed by the excessive expansion of the high-concentration PDMS layer, and at the same time can retain the good bonding between the PMMA layer and the PDMS layer. Through this rigid and flexible modified layer design, firstly, the dispersibility of the particles in the PET resin can be improved, secondly, the agglomeration of the particles in the PET resin can be avoided, and thirdly, the mechanical properties of the particles and the polyester film can be improved, and the grafted layer is not easy to crack.

[0022] 2. The graded shear blending, by gradually increasing the shear rate and blending temperature, can further avoid the interfacial stress concentration caused by the excessive expansion of PDMS, prevent the double-modified nano-titanium dioxide particles from cracking, and further improve the stability of the particles in the polyester film production process. DETAILED DESCRIPTION

[0023] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0024] A method for preparing a reinforced biaxially oriented polyester film comprises the following steps: A method for preparing a reinforced biaxially oriented polyester film comprises the following steps: Step 1: pretreating the nano titanium dioxide particles and uniformly dispersing the nano titanium dioxide particles; Step 2: performing PMMA grafting treatment on the pretreated nano-titanium dioxide particles; Step 3: dip-coating the PMMA-grafted nano-titanium dioxide particles layer by layer in 10wt%, 15wt%, and 20wt% PDMS solutions in turn to obtain double-modified nano-titanium dioxide particles; Step 4: Add the double modified nano titanium dioxide particles into the PET resin and perform graded shear blending; Step 5: Optimize the biaxial stretching of the blended PET resin.

[0025] The enhanced biaxially oriented polyester film comprises: PET resin; double-modified nano titanium dioxide particles are uniformly dispersed in the PET resin; The surface of the double-modified nano titanium dioxide particles is grafted with a PMMA layer, and the PMMA layer is coated with a PDMS layer outside; a first transition layer and a second transition layer are sandwiched between the PMMA layer and the PDMS layer, and the PDMS content in the second transition layer is higher than that in the first transition layer; Among them, PET resin 94-98wt%; nano titanium dioxide particles 0.1-5wt%; PMMA polymer 1-2wt%; PDMS polymer 0.5-2%; platinum-based catalyst 0.005-0.05%.

[0026] The specific steps of step 1 are: Nano-titanium dioxide particles were added into anhydrous ethanol and dispersed by ultrasonic for 20 minutes to ensure that the nano-particles were evenly dispersed.

[0027] The specific steps of step 2 are: Step 21: Add MMA to the pretreated nano-titanium dioxide solution and continue to stir evenly; Step 22: Add AIBN as an initiator, maintain the solution temperature at 60°C-75°C, and stir under the protection of protective gas. The reaction lasts for 3-5 hours. This step will generate PMMA chains and graft them onto the surface of nano-titanium dioxide particles; Step 23: After the reaction in step 22 is completed, the solvent is removed by rotary evaporation to obtain grafted modified nano titanium dioxide particles, and the particles are dried at 55°C-65°C for 12 hours to ensure that the ethanol is completely evaporated.

[0028] The specific steps of step 3 are: Step 31: immersing the grafted modified nano-titanium dioxide particles into a 10wt% PDMS solution for dip coating, and adding 0.01-0.05wt% of a platinum-based catalyst into the solution to promote cross-linking, wherein the dip coating speed is 1-5mm / s and the pulling speed is 1-2mm / s; Step 32: Curing the dip-coated nano-titanium dioxide particles at 70-80° C. for 10 minutes; Step 33: Replace the concentration of the PDMS solution with 15wt% and 20wt% respectively, and repeat steps 31 and 32 to obtain double-modified nano-titanium dioxide particles.

[0029] The specific steps of step 4 are: Step 41: Add the double modified nano titanium dioxide particles and pet resin into the blender, set the screw speed to 255-265 rpm, control the temperature to 270-280°C, and maintain for 5-10 minutes; Step 42: After completing step 41, set the screw speed to 270-285 rpm and the temperature to 280-290°C for 5-20 minutes; Step 43: After completing step 42, control the blender to slowly reach room temperature to complete the mixing of the double-modified nano titanium dioxide particles and PET.

[0030] The specific steps of step 5 are: Step 51: The mixed PET material is extruded into a film through a casting machine to initially form a PET film. Step 52: The PET film is stretched for the first time on a longitudinal stretching machine, the temperature is set to 80-100°C, and the film is longitudinally stretched in a heated and softened state, and the stretching ratio is 3-4 times; Step 53: After longitudinal stretching, the PET film is placed in a transverse stretching device, the temperature is set to 80-90°C, the transverse stretching ratio is set to 3-4 times, the film is quickly cooled after transverse stretching, and heat-set and cooled to obtain a finished biaxially stretched polyester film.

[0031] Among them, PMMA polymer is polymethyl methacrylate, PDMS polymer is polydimethylsiloxane, AIBN is azobisisobutyronitrile; MMA is methyl methacrylate.

[0032] A reinforced biaxially oriented polyester film, comprising PET resin: The PET resin is uniformly dispersed with double-modified nano titanium dioxide particles; The surface of the double-modified nano titanium dioxide particles is grafted with a PMMA layer, and the PMMA layer is coated with a PDMS layer on the outside; Among them, PET resin 94-98wt%; nano titanium dioxide particles 0.1-5wt%; PMMA polymer 1-2%; PDMS polymer 0.5-2%; platinum-based catalyst 0.005-0.05%.

[0033] The average particle size of the modified nano titanium dioxide particles is 20-50 nm.

[0034] The content of the modified nano titanium dioxide particles is 0.1-5wt%.

[0035] The polyester film is subjected to biaxial stretching treatment, with the stretching ratio being 3.5 times in the longitudinal direction and 3 times in the transverse direction. Example

[0036] Components: PET resin 96wt%, nano titanium dioxide particles 2wt%, PMMA polymer 1wt%, PDMS polymer 1wt%, platinum-based catalyst 0.01wt% The weight composition of the PMMA is calculated based on the weight composition of the added MMA, wherein the weight of the added MMA is equal to the weight of the PMMA polymer. It should be noted that the platinum-based catalyst is a Castaplatin catalyst.

[0037] Nano-titanium dioxide particle grafting modification: (1) Add 5 g of nano-titanium dioxide particles into 100 ml of anhydrous ethanol and disperse them by ultrasonic for 20 minutes; (2) Add 2 g MMA to the pretreated nano-titanium dioxide solution and continue stirring for 10 minutes until it is uniform; (3) Add 0.1 g AIBN as an initiator, maintain the temperature at 70°C, and stir under nitrogen protection. Continue the reaction for 3 hours to obtain nano-titanium dioxide particles with a PMMA grafted layer.

[0038] Coating modification of nano titanium dioxide particles: (1) Immersing the grafted modified nano-titanium dioxide particles in a 10wt% PDMS solution for dip coating, and adding 0.01-0.05wt% of a platinum-based catalyst to the solution to promote cross-linking, wherein the dipping speed is 1-5mm / s and the pulling speed is 1-2mm / s; (2) curing the dip-coated nano-titanium dioxide particles at 70-80° C. for 10 minutes; (3) The concentration of the PDMS solution was replaced with 15 wt % and 20 wt % respectively, and steps 31 and 32 were repeated to obtain double-modified nano-titanium dioxide particles.

[0039] The double modified nano titanium dioxide particles are mixed with pet resin and stretched into shape: (1) Add the double modified nano titanium dioxide particles and PET resin into the blender, adjust the speed to 255 rpm, control the temperature at 270 °C, and maintain for 10 minutes; (2) After completing step (1), change the speed to 285 rpm and control the temperature at 280°C for 20 minutes; (3) After completing step (2), the blender is controlled to reach room temperature, and the blended PET resin is stretched 3 times in the longitudinal direction and 3 times in the transverse direction. The stretching temperature is set to 90°C. After stretching, the film is cooled, heat-set, and cooled again to obtain a finished biaxially oriented polyester film.

[0040] After testing, the tensile strength of the biaxially oriented polyester film obtained in this embodiment is 120 MPA, the puncture strength is 235 N / mm, and the impact strength is 7.35 kj / mm. The transparency is good and it is suitable for packaging or display materials. It should be noted that in this embodiment, the blender is a twin-screw vacuum exhaust blender. Example

[0041] The difference between this embodiment and embodiment 1 is that the components are different, wherein: PET resin 94 wt%, nano titanium dioxide particles 3 wt%, PMMA polymer 1.5 wt%, PDMS polymer 1.45 wt%, platinum-based catalyst 0.05 wt% Through testing, the puncture strength of the biaxially oriented polyester film in this embodiment is 242N / mm, and the impact strength is 7.8kj / , with better transparency. Example

[0042] The difference between this embodiment and embodiment 1 is that the components are different, wherein: PET resin 97 wt%, nano-titanium dioxide particles 0.5 wt%, PMMA polymer 1.5wt%, PDMS polymer 1wt%, platinum-based catalyst 0.005wt%.

[0043] Through testing, the impact strength of the biaxially oriented polyester film in this embodiment is 6.3 kj / The puncture strength is 220N / mm, the transparency is good, it is suitable for packaging materials, and the puncture resistance is relatively low. Example

[0044] The difference between this embodiment and embodiment 1 is that the components are different, wherein: PET resin 95 wt%, nano titanium dioxide particles 4 wt%, PMMA polymer 0.75 wt%, PDMS polymer 0.2 wt%, platinum-based catalyst 0.05 wt% Through testing, the puncture strength of the biaxially oriented polyester film in this embodiment is 315N / mm, and the impact strength is 8.5kj / The transparency is slightly poor, and the dispersion of nano titanium dioxide particles is relatively low. Due to the high titanium dioxide content, the puncture resistance is better and it is suitable for industrial or protective materials. Example

[0045] The difference between this embodiment and embodiment 1 is that the components are different, wherein: PET resin 97.5 wt%, nano-titanium dioxide particles 1 wt%, PMMA polymer 0.75 wt%, PDMS polymer 0.7wt%, and platinum-based catalyst 0.05wt%.

[0046] Through testing, the puncture strength of the biaxially oriented polyester film in this embodiment is 225N, and the impact strength is 7.9kj / , moderate transparency, medium puncture resistance, suitable for outdoor use scenarios.

[0047] Comparative Example 1: The biaxially oriented polyester film without nano titanium dioxide particles has a stretching ratio and a molding process consistent with that of Example 1, and a puncture strength of 156 N / mm and an impact strength of 5.3 kj / mm. .

[0048] Comparative Example 2: The biaxially stretched polyester film with unmodified nano titanium dioxide particles has a stretching ratio and a molding process consistent with that of Example 1, and a puncture strength of 197 N / mm and an impact strength of 6.2 kj / mm. .

[0049] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A method for preparing a reinforced biaxially oriented polyester film, characterized in that: The following steps are involved: Step 1: pretreating the nano titanium dioxide particles and uniformly dispersing the nano titanium dioxide particles; Step 2: performing PMMA grafting treatment on the pretreated nano-titanium dioxide particles; Step 3: dip-coating the PMMA-grafted nano-titanium dioxide particles layer by layer in 10wt%, 15wt%, and 20wt% PDMS solutions in turn to obtain double-modified nano-titanium dioxide particles; Step 4: adding the double modified nano titanium dioxide particles into the pet resin and performing graded shear blending; Step 5: Optimize the biaxial stretching of the blended PET resin; The enhanced biaxially oriented polyester film comprises: PET resin; double-modified nano titanium dioxide particles are uniformly dispersed in the PET resin; The surface of the double-modified nano titanium dioxide particles is grafted with a PMMA layer, and the PMMA layer is coated with a PDMS layer outside; a first transition layer and a second transition layer are sandwiched between the PMMA layer and the PDMS layer, and the PDMS content in the second transition layer is higher than that in the first transition layer; Among them, PET resin 94-98wt%; nano titanium dioxide particles 0.1-5wt%; PMMA polymer 1-2wt%; PDMS polymer 0.5-2wt%; platinum-based catalyst 0.005-0.05wt%.

2. The method for preparing a reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific steps of step 1 are: Nano-titanium dioxide particles were added to anhydrous ethanol and dispersed using ultrasound for 20 min to ensure that the nano-particles were evenly dispersed.

3. The method for preparing a reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific steps of step 2 are: Step 21: Add MMA to the pretreated nano-titanium dioxide solution and continue to stir evenly; Step 22: Add AIBN as an initiator, maintain the solution temperature at 60°C-75°C, and stir under the protection of protective gas. The reaction lasts for 3-5 hours. This step will generate PMMA chains and graft them onto the surface of nano-titanium dioxide particles; Step 23: After the reaction in step 22 is completed, the solvent is removed by rotary evaporation to obtain grafted modified nano titanium dioxide particles, and the particles are dried at 55°C-65°C for 12 hours to ensure that the ethanol is completely evaporated.

4. The method for preparing a reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific steps of step 3 are: Step 31: immersing the grafted modified nano-titanium dioxide particles into a 10wt% PDMS solution for dip coating, and adding 0.01-0.05wt% of a platinum-based catalyst into the solution to promote cross-linking, wherein the dip coating speed is 1-5mm / s and the pulling speed is 1-2mm / s; Step 32: Curing the dip-coated nano-titanium dioxide particles at 70-80° C. for 10 minutes; Step 33: Replace the concentration of the PDMS solution with 15wt% and 20wt% respectively, and repeat steps 31 and 32 to obtain double-modified nano-titanium dioxide particles.

5. The method for preparing a reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific steps of step 4 are: Step 41: Add the double modified nano titanium dioxide particles and pet resin into the blender, set the screw speed to 255-265 rpm, control the temperature to 270-280°C, and maintain for 5-10 minutes; Step 42: After completing step 41, set the screw speed to 270-285 rpm and the temperature to 280-290°C for 5-20 minutes; Step 43: After completing step 42, control the blender to slowly reach room temperature to complete the mixing of the double-modified nano titanium dioxide particles and the PET resin.

6. The method for preparing a reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific steps of step 5 are: Step 51: Extruding the mixed PET resin material into a film through a casting machine to preliminarily form a PET film; Step 52: The PET film is stretched for the first time on a longitudinal stretching machine, the temperature is set to 80-100°C, and the film is longitudinally stretched in a heated and softened state, and the stretching ratio is 3-4 times; Step 53: After longitudinal stretching, the PET film is placed in a transverse stretching device, the temperature is set to 80-90°C, the transverse stretching ratio is set to 3-4 times, the film is quickly cooled after transverse stretching, and heat-set and cooled to obtain a finished biaxially stretched polyester film.

7. The reinforced biaxially oriented polyester film according to claim 1, characterized in that: The average particle size of the double-modified nano titanium dioxide particles is 20-50 nm.

8. The reinforced biaxially oriented polyester film according to claim 1, characterized in that: The specific surface area of ​​the double modified nano titanium dioxide particles is 110-120 / g.

9. The reinforced biaxially oriented polyester film according to claim 1, characterized in that: The polyester film is subjected to biaxial stretching treatment, with the stretching ratio being 3.5 times in the longitudinal direction and 3 times in the transverse direction.

Citation Information

Patent Citations

  • Grafting nano-titania particle and preparation thereof

    CN101353180B

  • A method for preparing nano-titanium dioxide, nano-titanium dioxide and its applications

    CN112645382B

  • Nanoparticle-biodegradable polyester film and preparation method thereof

    CN116218165A

  • Method for preparing grafted nano titanium oxide functional particles

    CN101161697A

  • Grafting nano-titania particle and preparation thereof

    CN101353180A